Apocalyptic public health: exploring discourses of fatness in childhood 'obesity' policy. Issue 1 (2nd January 2020) - Gillborn, Sarah; Rickett, Bridgette; Muskett, Tom; Woolhouse, Maxine
ABSTRACT: Recent 'obesity' preventions focus heavily on children, widely regarded as the future of society. The National Child Measurement Programme (NCMP) is a flagship government programme in England that annually measures the Body Mass Index (BMI) of children in Reception (aged 4–5) and Year 6 (aged 10–11) in order to identify 'at risk' children and offer advice to parents. Using Foucauldian discourse analysis this study explores how discourses within the programme construct fatness. The NCMP materials contain three key interrelated themes (concerning the hidden threat of 'obesity', the burden of 'obesity', and bodies that pose a greater risk) that combine to construct a 'grotesque discourse' of apocalyptic public health. 'Obesity' is constructed as a social and economic catastrophe where certain bodies pose a greater threat than others. We argue that this discourse has the potential to change health service policy in markedly regressive ways that will disproportionately impact working-class, Black, Asian, and mixed race families.